Inquérito soroepidemiológico do vírus da anemia infecciosa equina e dos coccídeos Sarcocystis neurona, Neospora spp. e Toxoplasma gondii em equinos do município de Rorainópolis, Roraima, Amazônia Setentrional brasileira - Spohr, Kledir Anderson Hofstaetter (2017)
Samples from 303 equines from 56 ranches of Rorainópolis municipality, state of Roraima were evaluated by means of the Indirect Immunofluorescence Test (IFAT) and to detect antibodies against Sarcocystis spp., Toxoplasma gondii e Neospora caninum. A subset of positive sample (n=15) against Sarcocystis spp. was evaluated by Western Blotting (WB) using crude antigen of S. neurona. Antibodies against p26 protein of the Equine Infectious Anemia Virus (EIAV) were detected through agar gel of immunodiffusion assay (AGID). From the serological result, possible risk factors were evaluated against individual or farming variables. The prevalence of antiSarcocystis spp. antibodies was estimated to be 43.2%, anti-Neospora sp. was 26.7%, anti-T. gondii was 18.5%, and anti-EIAV was 9,57%. Fourteen samples (14/15) evaluated by WB were positive for S. neurona antigens. From the ranches, 76.8% (43/56) presented at least one positive animal for Sarcocystis spp., 69.6% (39/56) for Neospora spp., 55.4% (31/56) for T. gondii, and 35,71% (20/56) for EIAV. Thirteen (14.3%) horses had antibodies against all coccidians agents, 50 (16.5%) had antibodies against Sarcocystis spp. and Neospora spp., 10 (3.3%) for Neospora spp. and T. gondii, and eight (2.6%) for Sarcocystis spp. and T. gondii. Associated variables (P≤0,05) to antibodies against Neospora spp. were do not feeding in rented pastures, absence of veterinary assistance in ranch, male horses, do not use stables and presence of herds up to 5 horses; while for T. gondii the contact with cats, the Lavradeiro breed, use of stables, raise of bovine in the ranch and presence of herds up to 5 horses were associated. There were no variables associated with the presence of antibodies against S. neurona e EIAV. Antibodies against S. neurona, Neospora spp. and T. gondii were reported for the first time in horses from the state of Roraima, located in the Northern Brazilian Amazon, highlighting to the elevate prevalence among ranches. This is the first study to use random samples for research of disease in Roraima state territory.